PERILAKU KONSUMSI PENGGUNA HP ANDROID SAMSUNG DI TOKO NEW ASLISEL KUALA SIMPANG MENURUT PERSPEKTIF EKONOMI ISLAM - Nona, dwi (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2020)
The purpose of consumption in Islam is not only satisfaction in the world but also the welfare of the hereafter to fulfill needs and not fulfill satisfaction / desires is the goal of Islamic economic activity this is what is also experienced by customers who buy Android phones at New Aslisel Stores with Samsung brands. These consumers use cell phones for the benefit of life activities and not just to improve social status, of course this is inseparable from people's consumption behavior, based on these problems, the researcher wants to examine in this thesis about "Consuming Behavior of Samsung Android Cellphone Users in New Stores Aslisel Kualasimpang According to Islamic Economic Perspective ". The problem in this thesis research is How is the consumption behavior of Samsung Android cellphone users in Kualanimpang New Aslisel Store from an Islamic economic perspective? What are the factors that influence the consumption behavior of Samsung Android HP users in Kualasimpang New Aslisel Store ?. The research in this thesis is included in the type of field research and literature with a qualitative approach with data collection techniques in the form of interviews and observations conducted on 8 respondents. Data analysis in this research is by reducing data, presenting data and drawing conclusions. The results of this study indicate that the material goals in the consumption behavior of buyers at the New Aslisel Kuala Simpang Shop are to facilitate and improve daily communication and help to complete daily work related to the profession they pursue while the spiritual goal is to increase knowledge religious through a video application on YouTube and can install prayer time reminder applications.